Enhanced optical output of GaN-based near-ultraviolet light-emitting diodes using an ultra-thin air cavity nanopatterned sapphire substrate. Issue 16 (30th March 2022) - Zhang, Gai; Chang, Le; Shao, Hua; Chu, Chunshuang; Fan, Chao; Zhang, Yandi; Zhang, Yonghui; Zhang, Zi-Hui
Abstract : A combined methodology is proposed to fabricate nanopatterned sapphire substrate with air cavity, which is used to improve the crystalline quality and light extraction efficiency of near-ultraviolet light-emitting diodes. Abstract : In this work, an ultra-thin air cavity nanopatterned sapphire substrate (UTAC-NPSS) is fabricated using a combined approach of nanosphere lens lithography, atomic layer deposition (ALD) and partial exposure lithography. The air cavity array with an ultra-thin Al2 O3 shell can be embodied into the GaN epitaxial layer by nanoscale epitaxial lateral overgrowth (NELOG). The Raman test results indicate that the UTAC-NPSS can well relax the compressive stress in the GaN epitaxial layer. At a driving current of 110 mA, the output power for the GaN-based near-ultraviolet light-emitting diodes (NUV LEDs) grown on the UTAC-NPSS is improved by 47% when compared with that of the LEDs grown on a flat sapphire substrate (FSS). This is because the UTAC-NPSS not only improves the crystalline quality but also enhances the light extraction efficiency (LEE). The enhanced LEE is further proven using a finite-difference time-domain (FDTD) simulation, which is attributed to the low refractive index of the ultra-thin air cavity structures.